Linear Programming Problems: Determination of Optimal Value of Real Life Practical Problems - Bhattarai, Dilaram (NUTA Journal, 2018)
Nowadays mathematical method are widely applied in planning of natural economy, organization of industry control, business decision, transportation, engineering, telecommunications, elaboration of military operations etc. From the general point of view, the problems of control and planning are usually reduced to a choice of a certain system of numerical parameters or a function ensuring the most effective achievement of the preplanned aim (optimum plan) with the limited possible resources taken into account. To estimate the effectiveness of a plan, introduce the plan quantity index expressed in term of the plan characteristics and attaining the extremism value for an optimal plan. For the large number of practically interesting problems the objective function is expressed linearly in term of plan characteristics, the permissible values of the parameters also obeying linear equalities or inequalities.